2005
DOI: 10.1080/00288330.2005.9517300
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal record of sewage outfall impacts on the inner Manukau Harbour, Auckland, New Zealand

Abstract: The fossil foraminiferal faunas preserved in intertidal sediment in six cores document the impact of human activities on the ecosystems of the north-east arm of the Manukau Harbour, Auckland, New Zealand. They indicate that Polynesian forest clearance and horticulture had negligible impact on the harbour biota. Before 1960, organic-rich discharges from four large meat works around the head of Mangere Inlet produced changes in nearby foraminiferal faunas but did not affect faunas in the more seaward part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The pollen sum was at least 250 grains, excluding Leptospermum type, herbaceous swamp plants and ferns except Pteridium (pollen was not counted in samples S7, S9 and SI1; slides were only scanned for cultigen pollen). Absence/presence of European-introduced pollen types were used to identify samples as pre-European or European (Hayward et al 2004, Matthews et al 2005. Following convention, common taxa are excluded from the base count for graphing purposes, but are still expressed as a percentage of the pollen sum.total, and may therefore exceed 100% in the pollen diagram.…”
Section: Methodsmentioning
confidence: 99%
“…The pollen sum was at least 250 grains, excluding Leptospermum type, herbaceous swamp plants and ferns except Pteridium (pollen was not counted in samples S7, S9 and SI1; slides were only scanned for cultigen pollen). Absence/presence of European-introduced pollen types were used to identify samples as pre-European or European (Hayward et al 2004, Matthews et al 2005. Following convention, common taxa are excluded from the base count for graphing purposes, but are still expressed as a percentage of the pollen sum.total, and may therefore exceed 100% in the pollen diagram.…”
Section: Methodsmentioning
confidence: 99%
“…New Zealand studies in the North Island harbors indicated that Polynesian forest clearance caused minor but initial ecological degradation starting at 1500 (Hayward et al 2006). European land clearance since~1840 and late-20th-century urbanization had a much larger impact on the marine ecosystem (Hayward et al 2004;Matthews et al 2005;Hayward et al 2006;Grenfell et al 2007;Hayward et al 2008). Details of North Island harbors' ecological degradation is complex and involves industrial and domestic sewage disposal, introduction of Asian date mussels and cordgrass, land clearance/deforestation, urbanization, and oyster farming (see, Hayward et al 2004;Matthews et al 2005;Hayward et al 2006;Grenfell et al 2007;Hayward et al 2008).…”
Section: Southern Hemisphere Watersmentioning
confidence: 99%
“…Many coastal areas were partially cleared of forest by pre-European Maori colonisers (700-200 years ago) but studies in estuarine and harbour cores indicate that this had only minor effects on sediment loads and foraminiferal faunas (e.g. Swales et al 2002a;Hayward et al 2004aHayward et al , 2006Matthews et al 2005). In the mid-late 19th century, after European colonisation, much of the native forest of northern New Zealand was more extensively cleared and converted to pastural farmland.…”
Section: Study Sitesmentioning
confidence: 96%